Investment Decisions and Their Impact on Job Creation at Energy Sector Enterprises in Poland - Kolegowicz, Konrad; Szymla, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The main objective of the research was to confirm the existence of a relationship between the investment outlays energy companies make and the number of workers they employ. The existence of this relationship would indicate the presence of a correlation between investment outlays and jobs created.Research Design & Methods: The objects of the research were energy companies operating in Poland divided into size classes (small, medium, large). To confirm the assumed research hypothesis, the rate of change of two quantities – capital expenditures and number of employees – was analysed in equivalent periods and taking into account the delay effect (t+1). The study of the relationship between quantities was done with correlation analysis. Linear regression analysis was used to simultaneously determine the level of interdependence of variables R2 and the Pearson coefficient.Findings: The results confirmed significant variation in the development over time of the two quantities, as well as their mutual relations divided into size classes of enterprises. The correlation analysis showed a low degree of interdependence in small and medium-sized enterprises and a high level in large ones. However, the negative direction of this interdependence in large enterprises was a surprise.Implications / Recommendations: The research results indicate that the high investment intensity in the energy sector results in an increase in the automation of manufacturing activities but does not necessarily involve changes in human resources. However, these relations may be differentiated by enterprise size classes.Contribution: The article contributes to the knowledge base on measures of enterprise development and the relationships between them. It could provide a methodological basis for conducting similar research in other industrial sectors.